Banking consolidation and small business lending - Elod Takáts (European Central Bank (ECB), 2004)
The paper investigates small business lending as an information problem. It models the effects of information asymmetries within the bank combined with fixed wages. Two kinds of inefficiencies arise in equilibrium: the credit officer either sometimes shirks or he is occasionally fired. In both cases lending falls below the first-best level. The solution, when the bank accepts the information asymmetries, is called the centralized structure. Under decentralized structure the bank employs additional supervisors to mitigate the information asymmetries within its organization. Decentralized banks manage to finance more small firms, but incur higher costs than centralized ones. Small banks are interpreted as a bank with relatively few credit officers, whom can be monitored without information asymmetries. The specification allows for investigating the effects of banking consolidation and technological change on small business lending. The model suggests that not banking size, but organizational structure is decisive in small business lending.
Keywords: G21; G34; J30; 330; banking; Corporate governance; efficiency wage; small business lending